A soybean-based adhesive with long open time and preparation method thereof

By using raw soybean powder and ammonium salt in soy-based adhesives, the problems of short opening time and fast viscosity growth are solved, longer opening time and more stable viscosity are achieved, and the production efficiency and glue performance of artificial boards are improved.

CN118389116BActive Publication Date: 2025-03-28NORTHEAST FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410568437.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-09
Publication Date
2025-03-28
Estimated Expiration
2044-05-09

AI Technical Summary

Technical Problem

The existing soybean-based adhesive has a short opening time and rapid viscosity growth, resulting in low production efficiency of artificial boards and unstable sheet bonding performance, limiting its large-scale industrial application.

Method used

By adding raw soybean powder and ammonium salt to the soybean based adhesive, the oil in the raw soybean powder forms a hydrophobic physical isolation layer, inhibiting the swelling of the defatted soybean powder by free water; the ammonium salt destroys hydrogen bonds and inhibits molecular recombination, and stabilizes the viscosity of the gel.

Benefits of technology

The opening time of soybean-based adhesive is extended, with an opening time of up to 68 minutes, meeting the glue coating and pre-pressing operation time requirements of artificial boards, improving production efficiency, and maintaining the viscosity of the glue within 5 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118389116B_ABST
    Figure CN118389116B_ABST
Patent Text Reader

Abstract

A soybean-based adhesive with a long open time and a preparation method thereof. The present invention relates to a soybean-based adhesive and a preparation method thereof. The present invention aims to solve the problem that the existing soybean-based adhesive has a short open time and a fast viscosity increase, which leads to low production efficiency of artificial boards and unstable bonding performance of boards, thus limiting its large-scale industrial application. The soybean-based adhesive with a long open time is prepared from an aqueous cross-linked resin solution, a polyether diol, defatted soybean powder, raw soybean powder and an ammonium salt; the preparation method is as follows: 1. Weighing; 2. Stirring the aqueous cross-linked resin solution and the polyether diol evenly to obtain an aqueous cross-linked dispersant solution; 3. Stirring the defatted soybean powder, raw soybean powder and ammonium salt evenly to obtain a composite modified soybean powder; 4. Stirring the aqueous cross-linked dispersant solution and the composite modified soybean powder evenly to obtain a soybean-based adhesive with a long open time. The present invention is used for a soybean-based adhesive with a long open time and its preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a soybean-based adhesive and a preparation method thereof. Background Art

[0002] Artificial boards are mainly made of wood units such as wood strips, veneers, wood shavings or wood fibers, which are bonded together with adhesives to form a wood-based composite material. Through the optimized combination of wood unit types and arrangements, molding conditions, adhesive types, etc., artificial boards with higher mechanical properties, better dimensional stability, and even isotropic properties can be prepared, making their performance better than solid wood. In addition, low-quality materials, inferior materials, branches, wood processing residues and other wood raw materials can be used for artificial board production. Therefore, artificial board production is a model of efficient and comprehensive utilization of wood. At present, artificial boards can completely replace solid wood and are widely used in furniture manufacturing, interior decoration, construction and engineering.

[0003] However, since more than 90% of artificial boards are formaldehyde-based synthetic resin adhesives, artificial boards and their products will release harmful formaldehyde during the production and use processes. They are the main source of formaldehyde pollution in the current human living environment, threatening people's lives and health and attracting widespread attention from the society.

[0004] Soybean-based adhesive is a major bio-based adhesive for the production of formaldehyde-free wood-based panels. Currently, industrialized soybean-based adhesives are mainly made from defatted soybean powder or soybean meal powder and cross-linked dispersant resin. They have the advantages of renewable raw materials, low carbon and environmental protection, no formaldehyde addition, and high bonding strength. They are the most promising bio-based adhesives in the future. In order for soybean-based adhesives to effectively replace formaldehyde-based synthetic resin adhesives in the future, they must be comparable to or better than urea-formaldehyde resins currently widely used in the wood-based panel industry in terms of performance, cost, process usability, and many other aspects. To this end, in the past decade, domestic and foreign scholars have conducted in-depth research on the application bottlenecks of traditional soybean-based adhesives, such as poor water resistance, high cost, easy mildew, high viscosity, and slow curing rate. Through chemical crosslinking, homogenization treatment, directional degradation, multi-level mildew prevention, hyperbranching modification, co-crosslinking enhancement, multi-network crosslinking enhancement and toughening, inorganic hybrid enhancement, filler enhancement of thermal conductivity, in-situ polymerization enhancement, pre-gel enhancement and pre-compression, bionic modification and synergistic modification, etc., the main application difficulties of traditional soybean-based adhesives have been effectively improved, and important breakthroughs have been achieved, such as the ability of adhesive products to withstand boiling water, long-term mildew and antibacterial, synergistic enhancement and toughening, significantly improved curing efficiency, and the cost of soybean-based adhesives being lower than urea-formaldehyde resins. These breakthroughs have met the needs of wood-based panel users for panel performance and the needs of wood-based panel manufacturers for adhesive cost reduction, and have realized the industrial application of related modified soybean-based adhesives.

[0005] However, since defatted soybean powder or soybean meal powder used in the production of soybean-based adhesives is a high molecular weight hydrophilic biomacromolecule, it is mixed with an aqueous cross-linking dispersant to form a glue solution. In the newly prepared glue solution, some soybean meal powder particles have not yet completely dissolved in the cross-linking dispersant solution. As the glue solution is placed, the undissolved soybean powder particles will continue to absorb the free water in the cross-linking dispersant solution to swell. The swollen defatted soybean powder or soybean meal powder further absorbs the free water with a diluting effect, causing the viscosity of the adhesive to increase significantly and rapidly, and lose wettability and adhesion due to the reduction of free water (commonly known as the "dry glue" phenomenon), which leads to the problem that the amount of glue applied to the board is difficult to accurately control, and the soybean-based adhesive sprayed on the veneer or board loses wettability and adhesion about 30 minutes after glue application.

[0006] Therefore, when using soybean-based adhesive to produce wood-based panels, the application of glue must be completed within 1-2 hours after the soybean-based adhesive is prepared, and the amount of glue applied must be adjusted in time during the application process to avoid the problem of inaccurate application caused by increased viscosity of the glue, improved adhesion, and increasing amount of glue applied; and it is also necessary to pre-press before the sprayed soybean-based adhesive loses its wettability and adhesion, that is, it is usually necessary to frequently switch the pre-pressing operation within 30 minutes of the gluing operation to avoid the board embryo not being able to be well pre-pressed and formed, which affects the bonding performance. As a result, the process requirements for the production of wood-based panels with soybean-based adhesives are very demanding, which not only reduces the production efficiency of wood-based panels, but also easily causes fluctuations in the bonding performance of the panels. Therefore, the open time of soy-based adhesives (the time from the start of adhesive coating to the time when it loses adhesion) is only about 30 minutes, which is significantly lower than that of urea-formaldehyde resin (usually greater than 2 hours). In addition, the viscosity of soy-based adhesives increases over time due to the continuous swelling of defatted soy powder due to water absorption. This makes it difficult for soy-based adhesives to adapt to the open time requirements (greater than 1 hour) for coating and pre-pressing operations in the current high-efficiency industrial production of wood-based panels. It is difficult for low-carbon and environmentally friendly soy-based bio-adhesives to effectively replace formaldehyde-based synthetic resins and achieve large-scale industrial applications.

[0007] Domestic and foreign literature research has found that there has been no research or report on extending the open time of soy-based adhesives. The short open time and unstable viscosity of soy-based adhesives have become a bottleneck problem for their large-scale industrial application. Summary of the invention

[0008] The present invention aims to solve the problem that the existing soybean-based adhesives have low production efficiency in artificial board production and unstable board bonding performance due to their short open time and rapid viscosity growth, which limits their large-scale industrial application, and further provide a soybean-based adhesive with a long open time and a preparation method thereof.

[0009] A soybean-based adhesive with a long open time is prepared from 100 parts of an aqueous cross-linked resin solution, 1 to 3 parts of a polyether diol, 30 to 45 parts of defatted soybean powder, 5 to 20 parts of raw soybean powder and 0.3 to 2.3 parts of an ammonium salt in parts by mass; the raw soybean powder accounts for 20% to 40% of the total mass of the defatted soybean powder and the raw soybean powder; and the ammonium salt accounts for 1% to 5% of the total mass of the defatted soybean powder and the raw soybean powder.

[0010] A method for preparing a soybean-based adhesive with a long open time is prepared according to the following steps:

[0011] 1. Weigh 100 parts of aqueous cross-linked resin solution, 1 part to 3 parts of polyether diol, 30 parts to 45 parts of defatted soy flour, 5 parts to 20 parts of raw soy flour and 0.3 parts to 2.3 parts of ammonium salt according to mass proportion; the raw soy flour accounts for 20% to 40% of the total mass of the defatted soy flour and the raw soy flour; the ammonium salt accounts for 1% to 5% of the total mass of the defatted soy flour and the raw soy flour;

[0012] 2. At room temperature, 100 parts of the aqueous cross-linked resin solution and 1 to 3 parts of the polyether diol are stirred evenly to obtain an aqueous cross-linked dispersant solution;

[0013] 3. Place 30 to 45 parts of defatted soybean powder, 5 to 20 parts of raw soybean powder and 0.3 to 2.3 parts of ammonium salt in a powder mixer and stir evenly to obtain composite modified soybean powder;

[0014] 4. Place the aqueous cross-linking dispersant solution and the composite modified soybean powder in a glue mixer and stir them evenly to obtain a soybean-based adhesive with a long open time.

[0015] The beneficial effects of the present invention are:

[0016] 1) The oil in the raw soybean powder forms a hydrophobic physical isolation layer on the surface of soybean protein, which inhibits the swelling of hydrophilic defatted soybean powder by free water, thereby reducing the viscosity-increasing effect caused by the mutual adsorption between the molecular chains of the defatted soybean powder and prolonging the open time. The strong polar ammonium salt destroys the hydrogen bonds and inhibits the molecular recombination to achieve the stabilization of the viscosity of the adhesive solution. The water-retaining and moisturizing hydroxyalkyl in its hydroxyalkyl ammonium salt prolongs the open time. The two work together to fully prolong the open time of conventional soybean-based adhesives, which can reach 68 minutes (an increase of 143%), meeting the requirements of the gluing and pre-pressing operation time of the soybean-based adhesive in the production of formaldehyde-free artificial boards, improving the industrial production efficiency of artificial boards, and at the same time keeping the viscosity of the adhesive solution stable within 5 hours (the viscosity increase is about 15%), so as to facilitate precise gluing.

[0017] 2) The long-open-time soybean-based adhesive prepared by the present invention based on the blending of functional components and their synergistic enhancement can effectively prolong the open time of the soybean-based adhesive, achieve stable viscosity of the adhesive liquid, and will not have an adverse effect on the bonding performance of the soybean-based adhesive. It is simple and easy to operate, has obvious effects, and is suitable for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The open time (A) and initial viscosity (B) of various soy-based adhesives prepared in Examples 1 to 2 and Comparative Experiments 1 to 4, a is Comparative Experiment 1, b is Comparative Experiment 2, c is Comparative Experiment 3, d is Comparative Experiment 4, e is Example 1, and f is Example 2;

[0019] Figure 2 Viscosity tracking of various soybean-based adhesives prepared in Examples 1 to 2 and Comparative Experiments 1 to 4, a is Comparative Experiment 1, b is Comparative Experiment 2, c is Comparative Experiment 3, d is Comparative Experiment 4, e is Example 1, and f is Example 2;

[0020] Figure 3 Appearance diagrams of the soybean-based adhesives prepared in Comparative Experiment 1, Comparative Experiment 2 and Example 2 after being placed for 0h and 3h, A is the newly prepared reference soybean-based adhesive of Comparative Experiment 1, B is the reference soybean-based adhesive of Comparative Experiment 1 after being placed at room temperature for 3h, C is the newly prepared soybean-based adhesive modified with raw soybean powder of Comparative Experiment 2, D is the soybean-based adhesive modified with raw soybean powder of Comparative Experiment 2 after being placed at room temperature for 3h, E is the newly prepared soybean-based adhesive with long open time of Example 2, and F is the soybean-based adhesive with long open time of Example 2 after being placed at room temperature for 3h;

[0021] Figure 4 is the water solubility of the defatted soy flour or composite modified soy flour in Examples 1 to 2 and Comparative Experiments 1 to 4, a is the defatted soy flour in Comparative Experiment 1, b is the composite modified soy flour prepared in Step 3 of Comparative Experiment 2, c is the composite modified soy flour prepared in Step 3 of Comparative Experiment 3, d is the composite modified soy flour prepared in Step 3 of Comparative Experiment 4, e is the composite modified soy flour prepared in Step 3 of Example 1, and f is the composite modified soy flour prepared in Step 3 of Example 2. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0023] Specific implementation method 1: This implementation method is a soybean-based adhesive with a long open time, which is prepared by 100 parts of aqueous cross-linked resin solution, 1 part to 3 parts of polyether diol, 30 parts to 45 parts of defatted soy flour, 5 parts to 20 parts of raw soy flour and 0.3 parts to 2.3 parts of ammonium salt in parts by mass; the raw soy flour accounts for 20% to 40% of the total mass of the defatted soy flour and the raw soy flour; the ammonium salt accounts for 1% to 5% of the total mass of the defatted soy flour and the raw soy flour.

[0024] The water-based cross-linked resin described in this specific embodiment is a commercially available cross-linked resin for soybean-based adhesives. One of its main functions is to produce chemical cross-linking with soybean powder to form a three-dimensional network cross-linked structure, which imparts bonding strength and water resistance; another main function is to disperse soybean powder to form a soybean-based adhesive with suitable viscosity and good fluidity to meet the requirements of operation such as flow, coating, wetting, adhesion, and pre-pressing of the adhesive. According to its cross-linking characteristics and the water resistance requirements of the produced board, the cross-linked resin is adjusted to a solid content concentration of 5% to 8% using water.

[0025] The polyether diol described in this specific embodiment mainly functions to achieve uniform and stable dispersion of soybean powder in soybean-based adhesive by utilizing its emulsification and hygroscopic properties, and has a certain moisturizing effect.

[0026] The main function of the raw soybean powder described in this specific embodiment is to provide hydrophobic oil to form a hydrophobic physical isolation layer on the surface of soybean protein, inhibit the swelling of hydrophilic defatted soybean powder by free water, reduce the mutual adsorption between the swollen and dissolved defatted soybean powder molecular chains through hydrogen bonds, thereby extending the open time of the soybean-based adhesive, reducing the initial viscosity of the prepared adhesive and stabilizing the viscosity.

[0027] One of the main functions of the ammonium salt is to use strongly polar ammonium ions as hydrogen bond acceptors, which can more effectively produce hydrogen bonding with hydrogen bond donors such as amino, hydroxyl, and carboxyl groups in the defatted soy powder component, thereby effectively destroying the intermolecular hydrogen bonding of soybean protein in the defatted soy powder and promoting protein dissolution. It can also hydrogen bond with the hydrogen bond donors of the defatted soy powder to produce a barrier effect, inhibiting the reconstruction of dissolved soybean protein molecular chains through hydrogen bonds and their mutual adsorption and recombination, thereby effectively reducing the initial viscosity of the soybean-based adhesive and achieving viscosity stability. In addition, the hydroxyalkyl ammonium salt can also provide hygroscopic hydroxyethyl or hydroxypropyl to achieve moisturizing and water retention, thereby extending the open time of the soybean-based adhesive.

[0028] The beneficial effects of this specific implementation are:

[0029] 1) The oil in the raw soybean powder forms a hydrophobic physical isolation layer on the surface of soybean protein, which inhibits the swelling of hydrophilic defatted soybean powder by free water, thereby reducing the viscosity-increasing effect caused by the mutual adsorption between the molecular chains of the defatted soybean powder and prolonging the open time. The strong polar ammonium salt destroys the hydrogen bonds and inhibits the molecular recombination to achieve the stabilization of the viscosity of the adhesive solution. The water-retaining and moisturizing hydroxyalkyl in its hydroxyalkyl ammonium salt prolongs the open time. The two work together to fully prolong the open time of conventional soybean-based adhesives, which can reach 68 minutes (an increase of 143%), meeting the requirements of the gluing and pre-pressing operation time of the soybean-based adhesive in the production of formaldehyde-free artificial boards, improving the industrial production efficiency of artificial boards, and at the same time keeping the viscosity of the adhesive solution stable within 5 hours (the viscosity increase is about 15%), so as to facilitate precise gluing.

[0030] 2) The soybean-based adhesive with a long open time prepared by the present specific embodiment based on the mixing of functional components and their synergistic enhancement can effectively extend the open time of the soybean-based adhesive, achieve stable viscosity of the adhesive liquid, and will not have an adverse effect on the bonding performance of the soybean-based adhesive. It is simple, easy to use, effective, and suitable for industrial applications.

[0031] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the solid content mass percentage concentration of the aqueous cross-linked resin solution is 5% to 8%; the aqueous cross-linked resin solution is a polyamide polyamine-epichlorohydrin resin solution or an aqueous epoxy resin solution. Other aspects are the same as specific embodiment 1.

[0032] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the polyether diol is a polyethylene oxide diol with an average relative molecular mass of 150 to 600. Other aspects are the same as specific implementation method 1 or 2.

[0033] Specific embodiment 4: This embodiment is different from the specific embodiments 1 to 3 in that: the raw bean powder is prepared according to the following steps: the raw beans are dried at a low temperature below 55°C to a moisture content of ≤10%, then peeled and crushed, and passed through a sieve of ≥100 meshes to obtain; the mass percentage of crude protein in the raw beans is ≥35%, and the mass percentage of oil is ≥16%. Others are the same as the specific embodiments 1 to 3.

[0034] Specific embodiment 5: This embodiment is different from Specific embodiments 1 to 4 in that: the defatted soy flour is obtained by physically crushing the residue after soybean oil extraction and then passing it through a 120-mesh screen; the mass percentage of crude protein in the defatted soy flour is ≥ 42%. Other aspects are the same as Specific embodiments 1 to 4.

[0035] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the ammonium salt is one or a mixture of hydroxyalkylammonium chloride, hydroxyalkylammonium bromide and inorganic ammonium salt. The rest is the same as specific embodiments 1 to 5.

[0036] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 56 in that: the hydroxyalkyl ammonium chloride is one of hydroxyethyl trimethyl ammonium chloride, hydroxypropyl trimethyl ammonium chloride, hydroxyethyl dodecyl dimethyl ammonium chloride and bis (2-hydroxyethyl) dimethyl ammonium chloride or a mixture of several thereof; the hydroxyalkyl ammonium bromide is one of hydroxyethyl trimethyl ammonium bromide, hydroxypropyl trimethyl ammonium bromide, dodecyl hydroxyethyl dimethyl ammonium bromide and dodecyl methyl dihydroxyethyl ammonium bromide or a mixture of several thereof; the inorganic ammonium salt is one of ammonium sulfate and ammonium chloride or a mixture of two thereof. The rest is the same as specific embodiments 1 to 6.

[0037] Specific embodiment eight: This embodiment is a method for preparing a soybean-based adhesive with a long open time, which is prepared according to the following steps:

[0038] 1. Weigh 100 parts of aqueous cross-linked resin solution, 1 part to 3 parts of polyether diol, 30 parts to 45 parts of defatted soy flour, 5 parts to 20 parts of raw soy flour and 0.3 parts to 2.3 parts of ammonium salt according to mass proportion; the raw soy flour accounts for 20% to 40% of the total mass of the defatted soy flour and the raw soy flour; the ammonium salt accounts for 1% to 5% of the total mass of the defatted soy flour and the raw soy flour;

[0039] 2. At room temperature, 100 parts of the aqueous cross-linked resin solution and 1 to 3 parts of the polyether diol are stirred evenly to obtain an aqueous cross-linked dispersant solution;

[0040] 3. Place 30 to 45 parts of defatted soybean powder, 5 to 20 parts of raw soybean powder and 0.3 to 2.3 parts of ammonium salt in a powder mixer and stir evenly to obtain composite modified soybean powder;

[0041] 4. Place the aqueous cross-linking dispersant solution and the composite modified soybean powder in a glue mixer and stir them evenly to obtain a soybean-based adhesive with a long open time.

[0042] Specific embodiment 9: This embodiment is different from specific embodiment 8 in that the stirring in step 4 is performed at a rotation speed of 300 rpm to 800 rpm for 10 to 15 minutes. The rest is the same as specific embodiment 8.

[0043] Specific embodiment 10: This embodiment differs from specific embodiment 8 or 9 in that the solid content of the soybean-based adhesive with a long open time described in step 4 is 30% to 40%. The rest is the same as specific embodiment 8 or 9.

[0044] The following examples are used to verify the beneficial effects of the present invention:

[0045] Example 1 (soybean-based adhesive compositely modified by raw soybean powder FSF-2-hydroxyethyltrimethylammonium chloride HTMC):

[0046] A soybean-based adhesive with a long open time is prepared from 100 parts by mass of an aqueous cross-linked resin solution, 1 part of a polyether diol, 40 parts of defatted soybean powder, 10 parts of raw soybean powder and 1 part of an ammonium salt.

[0047] The solid content of the aqueous cross-linked resin solution is 6% by mass; the aqueous cross-linked resin solution is a commercially available polyamide polyamine-epichlorohydrin resin solution.

[0048] The polyether diol is a polyoxyethylene diol with an average relative molecular mass of 600.

[0049] The raw bean powder is specifically prepared according to the following steps: at a temperature of 45° C., black beans are low-temperature dried to a moisture content of 8.4%, then peeled and crushed, and passed through a 100-mesh sieve to obtain the raw bean powder; the mass percentage of crude protein in the black beans is 35% to 40%, and the mass percentage of oil is 16% to 20%.

[0050] The defatted soy flour is commercially available defatted soy flour, which is obtained by physically crushing the residue after soybean oil extraction (soybean meal) and then passing it through a 120-mesh screen; the mass percentage of crude protein in the defatted soy flour is 43% to 55%.

[0051] The ammonium salt is 2-hydroxyethyltrimethylammonium chloride.

[0052] The method for preparing the above-mentioned soybean-based adhesive with a long open time is prepared according to the following steps:

[0053] 1. Weigh 100 parts of aqueous cross-linking resin solution, 1 part of polyether diol, 40 parts of defatted soy flour, 10 parts of raw soy flour and 1 part of ammonium salt according to mass proportions;

[0054] 2. At room temperature, 100 parts of the aqueous cross-linked resin solution and 1 part of the polyether diol were stirred evenly to obtain an aqueous cross-linked dispersant solution;

[0055] 3. Place 40 parts of defatted soybean powder, 10 parts of raw soybean powder and 1 part of ammonium salt in a powder mixer and stir evenly to obtain composite modified soybean powder;

[0056] Fourth, the aqueous cross-linking dispersant solution and the composite modified soybean powder are placed in a glue mixer and stirred evenly to obtain a soybean-based adhesive with a long open time, namely, FSF-HTMC modified soybean glue.

[0057] The stirring in step 4 is specifically stirring for 10 minutes at a rotation speed of 800 rpm.

[0058] The solid content of the soybean-based adhesive with a long open time described in step 4 is 35.3%.

[0059] Example 2 (soybean-based adhesive compositely modified by raw soybean flour FSF-dodecylmethyl dihydroxyethyl ammonium bromide DHDMB-ammonium chloride AC):

[0060] A soybean-based adhesive with a long open time is prepared from 100 parts by mass of an aqueous cross-linked resin solution, 1 part of a polyether diol, 40 parts of defatted soybean powder, 10 parts of raw soybean powder, 1 part of dodecylmethyl dihydroxyethyl ammonium bromide and 1.2 parts of ammonium chloride.

[0061] The solid content of the aqueous cross-linked resin solution is 6% by mass; the aqueous cross-linked resin solution is a commercially available polyamide polyamine-epichlorohydrin resin solution.

[0062] The polyether diol is a polyoxyethylene diol with an average relative molecular mass of 400.

[0063] The raw soybean powder is specifically prepared according to the following steps: at a temperature of 45° C., the soybeans are low-temperature dried to a moisture content of 9.1%, then peeled and crushed, and passed through a 100-mesh sieve to obtain the raw soybean powder; the mass percentage of crude protein in the soybeans is 35% to 42%, and the mass percentage of oil is 18% to 20%.

[0064] The defatted soy flour is commercially available defatted soy flour, which is obtained by physically crushing the residue after soybean oil extraction (soybean meal) and then passing it through a 120-mesh screen; the mass percentage of crude protein in the defatted soy flour is 43% to 55%.

[0065] The method for preparing the above-mentioned soybean-based adhesive with a long open time is prepared according to the following steps:

[0066] 1. Weigh 100 parts of aqueous cross-linking resin solution, 1 part of polyether diol, 40 parts of defatted soy flour, 10 parts of raw soy flour, 1 part of dodecylmethyl dihydroxyethyl ammonium bromide and 1.2 parts of ammonium chloride according to mass proportions;

[0067] 2. At room temperature, 100 parts of the aqueous cross-linked resin solution and 1 part of the polyether diol were stirred evenly to obtain an aqueous cross-linked dispersant solution;

[0068] 3. Place 10 parts of raw soybean powder, 40 parts of defatted soybean powder, 1 part of dodecylmethyl dihydroxyethyl ammonium bromide and 1.2 parts of ammonium chloride in a powder mixer and stir evenly to obtain a composite modified soybean powder;

[0069] Fourth, the aqueous cross-linking dispersant solution and the composite modified soybean powder are placed in a glue mixer and stirred evenly to obtain a soybean-based adhesive with a long open time, namely, FSF-DHDMB-AC modified soybean glue.

[0070] The stirring in step 4 is specifically stirring for 10 minutes at a rotation speed of 800 rpm.

[0071] The solid content of the soybean-based adhesive with a long open time described in step 4 is 35.9%.

[0072] Comparative experiment 1 (reference soybean-based adhesive):

[0073] The reference soybean-based adhesive is prepared from 100 parts of aqueous cross-linking resin solution, 1 part of polyether diol and 50 parts of defatted soybean flour in parts by mass.

[0074] The solid content of the aqueous cross-linked resin solution is 6% by mass; the aqueous cross-linked resin solution is a commercially available polyamide polyamine-epichlorohydrin resin solution.

[0075] The polyether diol is a polyoxyethylene diol with an average relative molecular mass of 400.

[0076] The defatted soy flour is commercially available defatted soy flour, which is obtained by physically crushing the residue after soybean oil extraction and then passing it through a 120-mesh sieve; the mass percentage of crude protein in the defatted soy flour is 43% to 55%.

[0077] The preparation method of the reference soybean-based adhesive is prepared according to the following steps:

[0078] 1. Weigh 100 parts of aqueous cross-linking resin solution, 1 part of polyether diol and 50 parts of defatted soy flour by mass;

[0079] 2. At room temperature, 100 parts of the aqueous cross-linked resin solution and 1 part of the polyether diol were stirred evenly to obtain an aqueous cross-linked dispersant solution;

[0080] 3. Place the aqueous cross-linking dispersant solution and 50 parts of defatted soybean flour in a glue mixer and stir evenly to obtain a reference soybean-based adhesive, namely, reference soybean glue.

[0081] The stirring in step 3 is specifically stirring for 10 minutes at a rotation speed of 800 rpm.

[0082] The solid content percentage of the reference soybean-based adhesive described in step 3 is 34.1%.

[0083] Comparative experiment 2 (soybean-based adhesive modified with raw soybean flour FSF):

[0084] The soybean-based adhesive modified by raw soybean powder FSF is prepared from 100 parts of aqueous cross-linking resin solution, 1 part of polyether diol, 35 parts of defatted soybean powder and 15 parts of raw soybean powder in parts by mass.

[0085] The solid content of the aqueous cross-linked resin solution is 6% by mass; the aqueous cross-linked resin solution is a commercially available polyamide polyamine-epichlorohydrin resin solution.

[0086] The polyether diol is a polyoxyethylene diol with an average relative molecular mass of 400.

[0087] The raw soybean powder is specifically prepared according to the following steps: at a temperature of 45° C., the soybeans are low-temperature dried to a moisture content of 7.2%, then peeled and crushed, and passed through a 160-mesh sieve to obtain the raw soybean powder; the mass percentage of crude protein in the soybeans is 35% to 42%, and the mass percentage of oil is 18% to 20%.

[0088] The defatted soy flour is commercially available defatted soy flour, which is obtained by physically crushing the residue after soybean oil extraction and then passing it through a 120-mesh sieve; the mass percentage of crude protein in the defatted soy flour is 43% to 55%.

[0089] The preparation method of the soy-based adhesive modified by raw soybean flour FSF is prepared according to the following steps:

[0090] 1. Weigh 100 parts of aqueous cross-linking resin solution, 1 part of polyether diol, 35 parts of defatted soy flour and 15 parts of raw soy flour according to mass proportions;

[0091] 2. At room temperature, 100 parts of the aqueous cross-linked resin solution and 1 part of the polyether diol were stirred evenly to obtain an aqueous cross-linked dispersant solution;

[0092] 3. Place 15 parts of raw soybean powder and 35 parts of defatted soybean powder in a powder mixer and stir evenly to obtain composite modified soybean powder;

[0093] Fourth, placing the aqueous cross-linking dispersant solution and the composite modified soybean powder in a glue mixer and stirring them evenly to obtain a soybean-based adhesive modified with raw soybean powder FSF, namely, FSF modified soybean glue.

[0094] The stirring in step 4 is specifically stirring for 10 minutes at a rotation speed of 800 rpm.

[0095] The solid content of the soybean-based adhesive modified with raw soybean flour FSF in step 4 is 32.4%.

[0096] Comparative experiment three (soybean-based adhesive modified by ammonium sulfate AS):

[0097] The ammonium sulfate AS modified soybean-based adhesive is prepared from 100 parts of an aqueous cross-linking resin solution, 1 part of a polyether diol, 38.8 parts of defatted soybean flour and 1.2 parts of ammonium sulfate in parts by mass.

[0098] The solid content of the aqueous cross-linked resin solution is 6% by mass; the aqueous cross-linked resin solution is a commercially available polyamide polyamine-epichlorohydrin resin solution.

[0099] The polyether diol is a polyoxyethylene diol with an average relative molecular mass of 200.

[0100] The defatted soy flour is commercially available defatted soy flour, which is obtained by physically crushing the residue after soybean oil extraction and then passing it through a 120-mesh sieve; the mass percentage of crude protein in the defatted soy flour is 43% to 55%.

[0101] The preparation method of the above-mentioned ammonium sulfate AS-modified soybean-based adhesive is prepared according to the following steps:

[0102] 1. Weigh 100 parts of aqueous cross-linking resin solution, 1 part of polyether diol, 38.8 parts of defatted soy flour and 1.2 parts of ammonium sulfate by mass;

[0103] 2. At room temperature, 100 parts of the aqueous cross-linked resin solution and 1 part of the polyether diol were stirred evenly to obtain an aqueous cross-linked dispersant solution;

[0104] 3. Place 38.8 parts of defatted soybean powder and 1.2 parts of ammonium sulfate in a powder mixer and stir evenly to obtain a composite modified soybean powder;

[0105] Fourth, placing the aqueous cross-linking dispersant solution and the composite modified soybean powder in a glue mixer and stirring them evenly to obtain the soybean-based adhesive modified with ammonium sulfate AS, namely AS modified soybean glue.

[0106] The stirring in step 4 is specifically stirring for 10 minutes at a rotation speed of 800 rpm.

[0107] The solid content of the soybean-based adhesive modified with ammonium sulfate AS described in step 4 is 31.6%.

[0108] Comparative experiment four (soybean-based adhesive modified with bis(2-hydroxyethyl)dimethylammonium chloride DHDMC):

[0109] The soybean-based adhesive modified by bis(2-hydroxyethyl)dimethylammonium chloride (DHDMC) is prepared from 100 parts of aqueous cross-linking resin solution, 1 part of polyether diol, 39 parts of defatted soybean powder and 1 part of bis(2-hydroxyethyl)dimethylammonium chloride by weight.

[0110] The solid content of the aqueous cross-linked resin solution is 6% by mass; the aqueous cross-linked resin solution is a commercially available polyamide polyamine-epichlorohydrin resin solution.

[0111] The polyether diol is a polyoxyethylene diol with an average relative molecular mass of 200.

[0112] The defatted soy flour is commercially available defatted soy flour, which is obtained by physically crushing the residue after soybean oil extraction and then passing it through a 120-mesh sieve; the mass percentage of crude protein in the defatted soy flour is 43% to 55%.

[0113] The preparation method of the above-mentioned bis(2-hydroxyethyl)dimethylammonium chloride DHDMC-modified soybean-based adhesive is prepared according to the following steps:

[0114] 1. Weigh 100 parts of aqueous cross-linking resin solution, 1 part of polyether diol, 39 parts of defatted soybean flour and 1 part of bis(2-hydroxyethyl)dimethylammonium chloride according to mass proportions;

[0115] 2. At room temperature, 100 parts of the aqueous cross-linked resin solution and 1 part of the polyether diol were stirred evenly to obtain an aqueous cross-linked dispersant solution;

[0116] 3. Place 39 parts of defatted soybean powder and 1 part of bis(2-hydroxyethyl)dimethylammonium chloride in a powder mixer and stir evenly to obtain a composite modified soybean powder;

[0117] Fourth, placing the aqueous cross-linking dispersant solution and the composite modified soybean powder in a glue mixer and stirring them evenly to obtain a soybean-based adhesive modified with bis(2-hydroxyethyl)dimethylammonium chloride DHDMC, namely, DHDMC-modified soybean glue.

[0118] The stirring in step 4 is specifically stirring for 10 minutes at a rotation speed of 800 rpm.

[0119] The solid content of the soybean-based adhesive modified with bis(2-hydroxyethyl)dimethylammonium chloride (DHDMC) in step 4 is 31.7%.

[0120] Effect evaluation: ① Open time: The soybean-based adhesives prepared in Examples 1 to 2 and Comparative Experiments 1 to 4 were respectively heated to 200 g / m 2The single-sided glue was evenly applied on one side of a 1.7mm thick flat poplar veneer, and then placed in an environment with a temperature of 24℃~26℃ and a relative humidity of 30%~45%. The time was counted from the time the veneer was coated with glue, and the time when the adhesive on the veneer completely lost its initial tack was recorded, which is the open time. The results are shown in the attached figure. Figure 1 As shown; Figure 1 The open time (A) and initial viscosity (B) of various soy-based adhesives prepared in Examples 1 to 2 and Comparative Experiments 1 to 4, a is Comparative Experiment 1, b is Comparative Experiment 2, c is Comparative Experiment 3, d is Comparative Experiment 4, e is Example 1, and f is Example 2.

[0121] ② Adhesive viscosity tracking and appearance state: The soy-based adhesives prepared in Examples 1 to 2 and Comparative Experiments 1 to 4 were placed at room temperature (23°C to 25°C) for 0h, 1h, 2h, 3h and 5h, and their viscosities were tested using a rotational viscometer (S4 rotor, speed 5rpm) after the adhesive was adjusted (the time at this time was recorded as 0h). The results are shown in the attached Figure 2 As shown; Figure 2 The viscosity tracking of various soybean-based adhesives prepared in Examples 1 to 2 and Comparative Experiments 1 to 4, a is Comparative Experiment 1, b is Comparative Experiment 2, c is Comparative Experiment 3, d is Comparative Experiment 4, e is Example 1, and f is Example 2. The appearance of the adhesives placed at room temperature for 0h and 3h was photographed, as shown in the attached figure. Figure 3 As shown; Figure 3 Appearance diagrams of the soybean-based adhesives prepared in Comparative Experiment 1, Comparative Experiment 2 and Example 2 after being placed for 0h and 3h, A is the newly prepared reference soybean-based adhesive in Comparative Experiment 1, B is the reference soybean-based adhesive in Comparative Experiment 1 after being placed at room temperature for 3h, C is the newly prepared soybean-based adhesive modified with raw soybean powder in Comparative Experiment 2, D is the soybean-based adhesive modified with raw soybean powder in Comparative Experiment 2 after being placed at room temperature for 3h, E is the newly prepared soybean-based adhesive with a long open time in Example 2, and F is the soybean-based adhesive with a long open time in Example 2 after being placed at room temperature for 3h.

[0122] ③ Adhesive properties: The soybean-based adhesives prepared in Examples 1 to 2 and Comparative Experiments 1 to 4 were mixed at 400 g / m 2 The double-sided glue amount was applied to both sides of the 1.7mm thick poplar veneer core board, and then the board embryo was formed in a way perpendicular to the wood grain direction. It was pre-pressed for 30min under the condition of veneer pressure of 0.6MPa, and then hot-pressed for 4.5min at a temperature of 120℃ and a veneer pressure of 0.6MPa to obtain a three-layer plywood. According to the method specified in the national standard GB / T 17657-2015, the dry strength and 63℃ blister strength (Type II bonding strength) of the plywood were tested respectively, and the results are shown in Table 1.

[0123] ④ Water solubility of soybean powder: take defatted soybean powder or composite modified soybean powder m1 (10±0.1g, accurate to 0.001g) with a moisture content of C%, add it to 90g water, immediately stir it at 24℃~26℃ with a mechanical stirring speed of 20rpm for 30min, then filter it with a dry filter paper weighed in advance, dry the residue at 103±2℃ to constant weight (m2, accurate to 0.001g), and measure the mass percentage of the component dissolved in water in the defatted soybean powder or composite modified soybean powder = (m1×C%-m2) / (m1×C%)×100%, that is, the water solubility, as shown in the attached Figure 4 As shown; Figure 4 is the water solubility of the defatted soy flour or composite modified soy flour in Examples 1 to 2 and Comparative Experiments 1 to 4, a is the defatted soy flour in Comparative Experiment 1, b is the composite modified soy flour prepared in Step 3 of Comparative Experiment 2, c is the composite modified soy flour prepared in Step 3 of Comparative Experiment 3, d is the composite modified soy flour prepared in Step 3 of Comparative Experiment 4, e is the composite modified soy flour prepared in Step 3 of Example 1, and f is the composite modified soy flour prepared in Step 3 of Example 2.

[0124] Table 1 Bonding properties of various soybean-based adhesives

[0125]

[0126]

[0127] The test results of comparative experiment 1 show that the open time of conventional soybean-based adhesive is only about 28 minutes, which is much lower than the open time required for gluing and pre-pressing operations in the current industrial production of wood-based panels (usually not less than 1 hour). In addition, its initial viscosity is large (75.1 Pa.s). The viscosity of the prepared adhesive increases rapidly during the placement process (increased to 184.3 Pa.s within 5 hours, an increase of 145%), which is not conducive to the precise control of the amount of glue applied. In addition, the appearance of the reference soybean-based adhesive changes from the initial homogeneous and fine adhesive (attached Figure 3 A) turns into a porridge-like paste (with Figure 3 B), which is mainly attributed to the fact that the undissolved defatted soybean powder in the prepared soybean-based adhesive continuously absorbs free water and swells during storage to form aggregation nuclei, which makes the dissolved high relative molecular weight soybean protein and its pre-crosslinked product with the cross-linked resin enriched and agglomerated near the aggregation nuclei.

[0128] The results of the comparative experiment 2 show that compared with the reference soybean-based adhesive prepared with defatted soybean powder alone, the soybean-based adhesive modified with raw soybean powder rich in protein and hydrophobic oil replacing part of the defatted soybean powder has an open time extended from 28min to 37min (an increase of 32%, with an increase of 1.3%. Figure 1 A), the initial viscosity decreased significantly (21% decrease, attached Figure 1B), the viscosity of the glue solution increased by 80% after being placed at room temperature for 5 hours (see Appendix Figure 2 ), which is significantly lower than the increase of 145% of the reference soybean-based adhesive. Moreover, after the adhesive was placed for 3h-5h, there was basically no porridge-like coagulant produced, maintaining the homogeneous and delicate appearance of the adhesive (see Appendix Figure 3 D). It can be seen that the use of raw soybean powder can significantly prolong the open time, reduce the viscosity of the adhesive, and improve the viscosity stability of the adhesive. This is attributed to the hydrophobic oil contained in the raw soybean powder, which forms a hydrophobic layer on the surface of the undissolved defatted soybean powder particles, inhibits the swelling of the undissolved defatted soybean powder by free water, reduces the formation of aggregation nuclei, and forms oil isolation between the soybean protein molecules dissolved in the adhesive, avoiding the formation of hydrogen bonds between the dissolved soybean protein molecular chains, thereby reducing the intermolecular adsorption between the swollen or dissolved soybean protein molecules during the static period through the formation of hydrogen bonds, and finally enables the soybean-based adhesive to retain free water for a longer time and prolong the open time. In addition, the isolation effect of the hydrophobic oil of raw soybean powder can be seen from the attached Figure 4 The water solubility of the composite bean powder decreased (from 42.1% to 40.6%, while the water solubility of raw soybean powder was 48.1%), which proved that: due to the presence of the hydrophobic isolation layer, free water was inhibited from entering the undissolved soybean powder, so that the water-soluble components in the defatted soybean powder could not be fully dissolved and dispersed in the free water outside the isolation layer, and the water solubility was reduced; in addition, reducing the amount of raw soybean powder reduced the hydrophobic oil content of the composite soybean powder system, which significantly reduced the effects of extending the open time of the soybean-based adhesive, reducing the viscosity of the glue and stabilizing the viscosity, which further confirmed the role of the hydrophobic oil of the raw soybean powder; in order to obtain a more obvious effect of extending the open time, reducing the viscosity of the glue and stabilizing the viscosity, the amount of raw soybean powder in the defatted soybean powder and raw soybean powder should not be less than 15%, preferably between 20% and 40%. It is the reduction in viscosity of the soybean-based adhesive modified with raw soybean powder that helps the glue to better wet the wood and penetrate into the pores of the wood, thereby also improving its bonding performance to a certain extent (Table 1).

[0129] The test results of comparative experiment 3 show that compared with the reference soybean-based adhesive prepared by using defatted soybean powder alone in comparative experiment 1, the use of a small amount of ammonium sulfate to modify defatted soybean powder can reduce the initial viscosity of the modified soybean-based adhesive from 75.1 Pa.s to 51.2 Pa.s (a decrease of 32%, Figure 1A), the effect is significantly better than the modification effect of using 30% (raw bean powder accounts for 30% of the total mass of defatted soy powder and raw bean powder) soybean flour in comparative experiment 2 (reduction of 21%); the viscosity increase of its modified soybean-based adhesive after 5 hours is only 41%, which is also significantly lower than the soybean-based adhesive modified with soybean flour (80%). However, the open time of the soybean-based adhesive modified with ammonium sulfate is only 33 minutes, which is about 18% higher than the reference adhesive in comparative experiment 1, but lower than the soybean-based adhesive modified with raw bean flour in comparative experiment 2 (37 minutes). It can be seen that the main function of ammonium sulfate is to use its small size and strong polarity as an ammonium ion as a hydrogen bond acceptor, which can more effectively produce hydrogen bonding with hydrogen bond donors such as amino, hydroxyl, and carboxyl groups in the defatted soy flour components, thereby effectively destroying the intermolecular hydrogen bonding of soybean protein in defatted soy flour, thereby promoting protein dissolution (the water solubility of defatted soy flour increased from 42.1% to 48.7% with only 3.1% ammonium sulfate addition, an increase of about 16%, and the addition of Figure 4 ), and can also hydrogen bond with the hydrogen bond donor of defatted soy flour to produce a barrier effect, inhibiting the reconstruction of dissolved soy protein molecular chains through hydrogen bonds and their mutual adsorption and reorganization, thereby effectively reducing the initial viscosity of the soy-based adhesive and achieving viscosity stability, but the effect of extending the open time of the soy-based adhesive is not as good as that of raw soy flour. The results in Table 1 show that the introduction of a small amount of inorganic ammonium salt will have a slight adverse effect on the bonding properties of the modified soy-based adhesive, but overall it is basically equivalent to the reference soy-based adhesive.

[0130] The test results of comparative experiment 4 show that compared with the reference soybean-based adhesive prepared by using defatted soybean powder alone in comparative experiment 1, the use of a small amount of bis(2-hydroxyethyl)dimethylammonium chloride to modify defatted soybean powder can extend the open time of the modified soybean-based adhesive from 28min to 40min (an increase of 43%, with an increase of 1.3%. Figure 1A), the improvement effect is better than the modification effect of using 30% (raw soybean powder accounts for 30% of the total mass of defatted soybean powder and raw soybean powder) raw soybean powder in comparative experiment 2 (increase of 32%) and the modification effect of using 3.1% ammonium sulfate in comparative experiment 3 (increase of 18%). However, the effect of reducing the viscosity and stabilizing the viscosity of soybean-based adhesives is not as good as 30% raw soybean powder and 3.1% ammonium sulfate. Compared with the ammonium sulfate in comparative experiment 3, the difference between the organic alkyl ammonium salt bis(2-hydroxyethyl) dimethyl ammonium chloride is that there are two hydrophilic hydroxyethyl groups and two weakly polar methyl groups. The hydroxyethyl group has the ability to absorb water and retain moisture, and the methyl group has a certain hydrophobic effect. The two are combined with the hydrophilic and strongly polar ammonium ions to destroy the hydrogen bonds between soybean protein molecules and promote the dissolution of soybean protein, so that the soybean-based adhesive can effectively lock free water and extend the open time. However, the hydroxyethyl and methyl groups of bis(2-hydroxyethyl)dimethylammonium chloride are sterically hindered, and they also weaken the hydrogen bond-destroying effect of strongly polar ammonium ions on soybean protein, resulting in an increase in the water solubility of defatted soybean powder modified with bis(2-hydroxyethyl)dimethylammonium chloride (from 42.1% to 45.8%, an increase of about 9%), but lower than ammonium sulfate without hydroxyethyl and methyl groups (48.7%).

[0131] The test results of Example 1 show that: compared with Comparative Experiment 2 and Comparative Experiment 4, the raw bean powder that can effectively reduce the viscosity and stabilize the viscosity is compounded with the organic hydroxyalkyl ammonium salt that can effectively prolong the open time. Even if the amount of raw bean powder is reduced (the raw bean powder accounts for the total mass of defatted soy powder and raw bean powder from 30% to 20%), and the amount of hydroxyalkyl ammonium salt is also reduced (the ammonium salt accounts for the total mass of defatted soy powder and raw bean powder from 3.1% to 2%), the composite modified soybean-based adhesive still has a more excellent open time (54min), which is about 93% longer than the reference soybean-based adhesive, and the initial viscosity of the adhesive is also significantly reduced (57.0Pa.s), which is slightly lower than that of the adhesive modified with 30% raw bean powder, and the viscosity stabilization ability of the adhesive is basically equivalent to that of 30% raw bean powder. It can be seen that the combination of raw soybean powder and hydroxyalkyl ammonium salt has a significant synergistic effect on extending the open time and reducing the initial viscosity, and the bonding performance of the composite modified soybean-based adhesive is much better than that of the reference adhesive (the water resistance of Class II is improved by about 19%). However, its open time is still shorter than the minimum gluing and pre-pressing operation time (≧1h) expected by the current industrial production of wood-based panels, and the viscosity increase of the modulated soybean-based adhesive after 3h-5h (from 57Pa.s to 110.2Pa.s, an increase of 93%) is still a bit large, which cannot meet the needs of industrial production of wood-based panels.

[0132] The test results of Example 2 show that when raw soybean flour that can effectively reduce viscosity and stabilize viscosity is compounded with inorganic ammonium salt that can effectively stabilize viscosity, and organic hydroxyalkyl ammonium salt that can simultaneously prolong the open time and stabilize viscosity, the raw soybean flour accounts for 20% of the total mass of defatted soybean flour and raw soybean flour, the hydroxyalkyl ammonium salt accounts for 2% of the total mass of defatted soybean flour and raw soybean flour, and the inorganic ammonium salt accounts for 2.4% of the total mass of defatted soybean flour and raw soybean flour. The soy-based adhesive obtained by the composite modification has a longer open time (68min), which is about 143% longer than the reference soy-based adhesive. Moreover, the initial viscosity of the glue solution is further significantly reduced to 38.6Pa.s, which is 35% lower than that of the 30% raw bean powder modified adhesive, and about 25% lower than that of the 3.1% ammonium sulfate modified adhesive. The viscosity stability ability of the glue solution is also significantly improved. The viscosity of the modulated soybean-based adhesive only increases by about 15% after being placed for 5 hours, which is significantly lower than the modification effect of using ammonium salt or raw bean powder alone in the comparative experiment 2 and the comparative experiment 3 (the viscosity growth within 5 hours is 41% to 80%) and the composite modification effect (93%) of raw bean powder and hydroxyalkyl ammonium salt in Example 1. It can be seen that the raw bean powder, organic hydroxyalkyl ammonium salt and inorganic ammonium compound have obvious synergistic effects on extending the open time, reducing the initial viscosity and stabilizing the viscosity of the glue solution, and the bonding performance of the composite modified soybean-based adhesive of the three has been greatly improved compared with the reference adhesive (the water resistance of Class II has been improved by about 16%). In particular, its open time is about 68 minutes, which basically meets the minimum gluing and pre-pressing operation time (1 hour) expected by the current industrial production of wood-based panels. Moreover, the viscosity increase of the prepared soy-based adhesive is minimal (about 15%) after being placed for 5 hours, which effectively guarantees the need for precise gluing in the production of wood-based panels.

Claims

1. A soybean-based adhesive with a long open time, characterized in that It is prepared from 100 parts of aqueous cross-linked resin solution, 1 to 3 parts of polyether diol, 30 to 45 parts of defatted soybean powder, 5 to 20 parts of raw soybean powder and 0.3 to 2.3 parts of ammonium salt in parts by mass; the raw soybean powder accounts for 20% to 40% of the total mass of the defatted soybean powder and the raw soybean powder; the ammonium salt accounts for 1% to 5% of the total mass of the defatted soybean powder and the raw soybean powder; The solid content of the aqueous cross-linked resin solution is 5% to 8% by mass; the aqueous cross-linked resin solution is a polyamide polyamine-epichlorohydrin resin solution; The polyether diol is a polyoxyethylene diol with an average relative molecular mass of 150 to 600; The ammonium salt is a mixture of one or a combination of hydroxyalkylammonium chloride and hydroxyalkylammonium bromide and an inorganic ammonium salt; The hydroxyalkyl ammonium chloride is one of hydroxyethyl trimethyl ammonium chloride, hydroxypropyl trimethyl ammonium chloride, hydroxyethyl dodecyl dimethyl ammonium chloride and bis (2-hydroxyethyl) dimethyl ammonium chloride or a mixture of several thereof; the hydroxyalkyl ammonium bromide is one of hydroxyethyl trimethyl ammonium bromide, hydroxypropyl trimethyl ammonium bromide, dodecyl hydroxyethyl dimethyl ammonium bromide and dodecyl methyl dihydroxyethyl ammonium bromide or a mixture of several thereof; the inorganic ammonium salt is one of ammonium sulfate and ammonium chloride or a mixture of two thereof; The raw bean powder is obtained by drying, peeling, crushing and sieving raw beans; the mass percentage of crude protein in the raw beans is ≥35%, and the mass percentage of oil is ≥16%; The defatted soy flour is obtained by physically crushing the residue after soybean oil is squeezed, and then passing it through a sieve with mesh size of ≥120; the mass percentage of crude protein in the defatted soy flour is ≥42%.

2. A soybean-based adhesive with a long open time according to claim 1, characterized in that The raw bean powder is specifically prepared according to the following steps: low-temperature drying the raw beans at below 55° C. to a moisture content of ≤10%, then peeling and crushing, and passing through a sieve of ≥100 meshes to obtain the raw bean powder.

3. The method for preparing a soybean-based adhesive with a long open time as claimed in claim 1, characterized in that It is prepared according to the following steps:

1. Weigh 100 parts of aqueous cross-linked resin solution, 1 part to 3 parts of polyether diol, 30 parts to 45 parts of defatted soy flour, 5 parts to 20 parts of raw soy flour and 0.3 parts to 2.3 parts of ammonium salt according to mass proportion; the raw soy flour accounts for 20% to 40% of the total mass of the defatted soy flour and the raw soy flour; the ammonium salt accounts for 1% to 5% of the total mass of the defatted soy flour and the raw soy flour; 2. At room temperature, 100 parts of the aqueous cross-linked resin solution and 1 to 3 parts of the polyether diol are stirred evenly to obtain an aqueous cross-linked dispersant solution; 3. Place 30 to 45 parts of defatted soybean powder, 5 to 20 parts of raw soybean powder and 0.3 to 2.3 parts of ammonium salt in a powder mixer and stir evenly to obtain composite modified soybean powder; 4. Place the aqueous cross-linking dispersant solution and the composite modified soybean powder in a glue mixer and stir them evenly to obtain a soybean-based adhesive with a long open time.

4. The method for preparing a soybean-based adhesive with a long open time according to claim 3, characterized in that The stirring uniformly described in step 4 specifically comprises stirring for 10 min to 15 min at a rotation speed of 300 rpm to 800 rpm.

5. The method for preparing a soybean-based adhesive with a long open time according to claim 3, characterized in that The solid content of the soybean-based adhesive with a long open time described in step 4 is 30% to 40%.

Citation Information

Patent Citations

  • Preparation method of bean flour plate core glue

    CN113512401A

  • Soybean meal adhesive for plywood and preparation method thereof

    CN115404009A